Utilization of waste cooking oil for highly efficient recovery of unburned carbon from coal fly ash. (1st February 2021) - Yang, Zili; Chang, Guohui; Xia, Yangchao; He, Qi; Zeng, Hongbo; Xing, Yaowen; Gui, Xiahui
Abstract: The disposal of industrial solids (e.g., coal fly ash (CFA)) and kitchen wastes (e.g., waste cooking oil (WCO)) has attracted much attention worldwide. However, it is challenging to manage these wastes economically. In this study, the potential of WCO as a collector to recover unburned carbon from CFA by froth flotation was investigated for the utilization of CFA and WCO resources. Traditional collectors, i.e., diesel oil and fresh cooking oil, were used for comparison. The composition of the collectors was determined via Fourier-transform infrared spectroscopy and gas chromatography/mass spectrometry. The interaction mechanisms between the CFA surface and different collectors were analyzed by atomic force microscopy, X-ray photoelectron spectroscopy, and dynamic contact angle measurements. The results indicate that WCO contains a large amount of oxygen-containing functional groups such as aldehydes, short-chain acids, and long-chain fatty acids. Furthermore, flotation tests indicated that in comparison with diesel oil and cooking oil as collectors, WCO can significantly enhance the recovery of unburned carbon from CFA and effectively lead to tailings with low loss on ignition. The major mechanism responsible for the enhanced CFA flotation is that its oxygen-containing functional groups, such as CO and COOH, were covered, whereas the C–H/C–C groups were exposed on the CFA surface due to the strong adhesion forces between the CFA and WCO under the synergistic effect of the short-chain acids/aldehydes and long-chain fatty acids in WCO. This resulted in a significant increase in the surface hydrophobicity of the CFA after the WCO treatment. This work provides an efficient and promising green method for the recovery of unburned carbon from CFA as well as the reuse of WCO, allowing the management of an industrial solid and kitchen waste. Graphical abstract: Analysis of traditional and novel recycling route of CFA and WCO. Image 1 Highlights: Waste cooking oil (WCO) was used as a novel coal fly ash (CFA) flotation collector. 84.28% of unburned carbon (UC) in CFA can be effectively recovered. Synergism of short-chain acids/long-chain fatty acids in WCO was found on CFA surface. Two wastes of WCO and CFA have been effectively reused and management.